Improvement of mechanical properties and corrosion resistance of 316L and 304 stainless steel by low temperature plasma cementation - Gobbi,Silvio José (2020)
ABSTRACT Low temperature plasma carburizing treatment of austenitic stainless steels is a carbon surface diffusion process for a surface hardness and corrosion and wear resistance. The process is carried out by introducing a mixture of carbon-containing gases and through the use of low temperatures the resulting cemented layer usually contains a single phase of supersaturated austenite with carbon – S-phase. For the present investigation, austenitic stainless steels AISI 316L and 304 were plasma cemented for 8 hours in the gas mixture containing 7.5% CH4 in H2, with a pressure of 500 Pa, at temperatures of 375 ºC and 450 ºC. The phases formed were determined by X-ray diffraction. The corrosion resistance was evaluated through immersion tests over time and cyclic voltammetry. The results indicate that there was no formation of compounds (carbides) in the cemented layer for both steels at any of the temperatures and there was a corrosion resistance improvement.